Analisis Peran Jasa Joki Dalam Pendaftaran Kartu Prakerja Di Kabupaten Kerinci - Azis, Saipul; Putra, Dontes; Meirison, Meirison; Novia, Aidil (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2024)
Pre-employment Card is a program that provides training cost assistance to Indonesian people who want to improve or have new skills. However, in the process of the emergence of the phenomenon of jockey services in pre-employment card registration. The purpose of this study is to determine the role of jockey services in pre-employment card registration in Kerinci Regency. This type of research is qualitative with a case study research approach. Primary data sources were obtained through interviews and observation methods. Based on the results of the study, the role of jockey services in pre-employment card registration in Kerinci Regency generally does not violate the principles of Islamic economics. This general thing can be seen where in principle justice, fairness, transparency, and integrity and desires have been fulfilled and the distribution of pre-employment card funds and wages does not contain elements of maisir, gharar and usury.